Emotional and behavioral features associated with subclinical hypothyroidism in children and adolescents with Down syndrome - Fucà, Elisa; Costanzo, Floriana; Galassi, Paolo; Celestini, Laura; Villani, Alberto; Valentini, Diletta; Vicari, Stefano (Frontiers in Psychology, 2024)
Background. Subclinical hypothyroidism (SH) is particularly frequent in individuals with Down syndrome (DS). Despite the amount of evidence suggesting SH is associated with psychopathological symptoms and sleep problems in general population, poor is known about the emotional and behavioral features associated with SH in children with DS. Objective. The first aim of the current study was to investigate differences in emotional and behavioral profiles between a group of children with DS exhibiting co-occurring SH and a group of age and BMI-matched children with DS without co-occurring SH. The second aim of the present study was to investigate differences in sleep disturbances between these groups. Methods. We included in this retrospective study 98 participants with DS aged 3-18 years with the aim to explore differences in emotional/behavioral problems as well as in sleep difficulties between children with DS with or without co-occurring SH. Results. Participants with co-occurring SH exhibited significantly higher scores at several scales of the Conners’ Parent Rating Scales Long Version – Revised. However, they did not exhibit more sleep problems than control group. Conclusions. These results provide specific indications for psychological and neuropsychiatric evaluation of children with DS with suspected or diagnosed SH, highlighting the importance of a multidisciplinary approach in clinical care for children and adolescents with DS.